The Role of Science Teachers in Inspiring The Younger Generation: Improving The Quality and Competence of Science Teachers - Nisa’i, Kamilia; Chandri, Fareza; Faizah, Fransiska; Zaenaf, Siti; Aulia, Fanesa Oktavianes; Hidayah, Nurul (Islamic Journal of Integrated Science Education (IJISE), 2024)
Science teachers are not only responsible for teaching the material, but also inspiring students' curiosity, critical thinking, and character. This research uses the literature study method to gather information from relevant academic sources, including peer-reviewed journals, academic books, and trusted publications. This research discusses the important role of science teachers in inspiring the younger generation and improving their quality and competence. Teachers' competence in planning, implementing and evaluating learning greatly affects student success. Competent teachers are able to create an effective learning environment, manage the classroom well and use various resources and technology to enrich students' learning experience. Competent and inspiring science teachers can help students reach their full potential through quality education. This can be achieved through continuous training, adoption of innovative teaching methods and dedication to educating. Thus, science teachers play an important role in preparing students to face future challenges and become agents of change in society.